1966
DOI: 10.1063/1.1754627
|View full text |Cite|
|
Sign up to set email alerts
|

FREQUENCY SPECTRUM OF GIANT ACOUSTIC WAVE PACKETS GENERATED IN CdS BY HIGH ELECTRIC FIELDS

Abstract: Using light scattering and the photoelastic effect, we have investigated the frequency spectrum of giant acoustic shear wave packets generated in semiconducting CdS by high electric fields. The frequencies were in the range 100 to 1500 MHz, at least an order of magnitude lower than the predicted frequency for maximum net gain. The strains were high enough to cause permanent crystal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The field was applied as single voltage pulses with a repetition rate well below one pulse per second in order to avoid crystal heating. Frequently, at high acoustic flux levels in the crystal, damage similar to that reported by Zucker and Zemon (12) was observed. When this occurred the current waveform was found to change.…”
Section: Methodssupporting
confidence: 68%
“…The field was applied as single voltage pulses with a repetition rate well below one pulse per second in order to avoid crystal heating. Frequently, at high acoustic flux levels in the crystal, damage similar to that reported by Zucker and Zemon (12) was observed. When this occurred the current waveform was found to change.…”
Section: Methodssupporting
confidence: 68%
“…Measurements were carried oVt on semiconducting CdS (p = 30 &2 cm) with the electric field applied along the c-axis (typical dimensionsA = 1 X 1 mm 2, L = 1.5 mm). From the threshold voltage defined by the onset of the current fluctuations [8], Brillouin scattering data and the knee-voltage in the current-voltage characteristic it was clear that transversal off-axis waves were amplified in accordance with earlier reports [9].…”
Section: A[a/(r~+iw)+c1 + A2 + U3~e K1k2l[exp(-ik1l)-exp(-ik2l)]supporting
confidence: 67%
“…This showed that even in the presence of large lattice losses a net gain can still be maintained with a drift velocity of electrons only slightly larger than us. Although in practice acoustic flux domains are not rectangular and contain several frequencies of acoustic waves (Zucker and Zemon 1966), the results of the calculations bring out the essential features of domain growth and current saturation. The actual shape and harmonic content of a domain would of course be very much determined by its origin.…”
Section: Discussionmentioning
confidence: 99%